Produção de etanol por hidrólise ácida de melaço de soja - Romão, Betânia Braz (2011)
The manufacture of soybean preparations rich in protein free of flatulent oligosaccharides as raffinose and stachyose generates an effluent that has considerable amounts of carbohydrates. In recent years the world has been watching a great interest in the use of agricultural residues in obtaining renewable fuels such as bioethanol. In the present work the use of this residue called molasses soybean was studied in processes of acidic hydrolysis followed by submerged fermentation by Saccharomyces cerevisiae. It was evaluated the influence of acid type, pH, and the absolute pressure of hydrolysis in ethanol yield and concentration of residual total sugar using a factorial design in which the pH ranged from 3 to 5, the absolute pressure ranged from 1 to 2 atm and acids studied were sulfuric, hydrochloric and nitric. Settled the hydrolysis time of 20 min, in 1:4 dilution of molasses (250 gmelaço/1000 gmeio) and fermentation time of 12 hours for the nitric acid and for 14 hours foil the sulfuric and hydrochloric acids on the basis of preliminary tests performed. The experiments occurred in a batch reactor Appplikon useful volume of 1.5 L, agitation speed 230 rpm and inoculum concentration 30 g/L with the volume of inoculum 30% of the total volume. The results of the factorial design showed that for all acids studied the central points of pH (4) and pressure (1.5 atm) were those with the highest ethanol yield being 46% for sulfuric acid, 48% for hydrochloric acid and 54% for nitric acid. Analyzing the contour curve defined the optimal working conditions for pH (4.5) and pressure (1.5 atm) to satisfy the hydrolysis and fermentation. As nitric acid showed the best ethanol yield was carried out a test to measure the concentration of inoculum in the fermentation and the concentrations tested were 25, 30, 35, 40 and 45 g/L. The chosen concentration was 35 g/L with a yield of 57%. Set all the conditions, it was carried out a kinetic study to assess for fermentation time and conditions were pH 4.5 hydrolysis and fermentation, absolute pressure of 1.5 atm hydrolysis, fermentation temperature 35 ± 0.5 °C shaker 230 rpm, inoculum concentration of 35 ± 0.2 g / L. The stabilization of ethanol production ocurred around ran 14 hours of fermentation with ethanol yield in relation to the initial sugar 62%. The soybean molasses fermentation was evaluated by removing the more concentrated ethanol in a rotary evaporator and fermenting the juice again. After three fermentations, ethanol yield in relation to the total sugar consumed was 73%.